Myoarchitecture and connective tissue in hearts with tricuspid atresia. Issue 2 (1st February 1999) - Sanchez-Quintana, D; Climent, V; Ho, S Y; Anderson, R H
Abstract : Objective: To compare the atrial and ventricular myoarchitecture in the normal heart and the heart with tricuspid atresia, and to investigate changes in the three dimensional arrangement of collagen fibrils. Methods: Blunt dissection and cell maceration with scanning electron microscopy were used to study the architecture of the atrial and ventricular musculature and the arrangement of collagen fibrils in three specimens with tricuspid atresia and six normal human hearts. Results: There were significant modifications in the myoarchitecture of the right atrium and the left ventricle, both being noticeably hypertrophied. The middle layer of the ventricle in the abnormal hearts was thicker than in the normal hearts. The orientation of the superficial layer in the left ventricle in hearts with tricuspid atresia was irregular compared with the normal hearts. Scanning electron microscopy showed coarser endomysial sheaths and denser perimysial septa in hearts with tricuspid atresia than in normal hearts. Conclusions: The overall architecture of the muscle fibres and its connective tissue matrix in hearts with tricuspid atresia differed from normal, probably reflecting modelling of the myocardium that is inherent to the malformation. This is in concordance with clinical observations showing deterioration in pump function of the dominant left ventricle from very early in life.